CASE REPORT AWARENESS TO PROLAPSE OF THE EYE IN BABY - Athi Purnasari; Ratna Doemilah; Ismi Zuhria (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2020)
Corneal perforation may be associated with prolapse of ocular tissue. We present a rare case reportan11 months-old female presented prolapsed of right eye. She was earlier diagnosedwithright corneal ulcer anddescemetocele. Physicalexamination revealed perforatedcornea.On ultrasound examination showedvitreous hazzinessand membranous opacity assumed due to inflammation. Based on examinationswe suspectedmalignancy process and performed enucleation withautogenous Dermis Fat Graft (DFG) which harvested onthigh region.Histopathology examination revealed chronic inflammation process.Hence, determining the causative factors of the prolapsed eye is the key for better management and prognosis.